2016
DOI: 10.1007/s10991-016-9182-2
|View full text |Cite
|
Sign up to set email alerts
|

Lesbian Spanners: A Re-appraisal of UK Consensual Sadomasochism Laws

Abstract: There continues to be legal invisibility of lesbians as sexual beings; in particular, for those lesbians who engage in BDSM. A cursory glance at work both within and outside of the academy gives the impression of increased social and legal acceptability for those who engage in BDSM. However, I suggest that this acceptance is illusory and that instead, gay men who engage in BDSM experience increased legal supervision and increased invisibility for lesbians. These issues are examined in the context of two seemin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
1
0
1
Order By: Relevance
“…Das erlaubte es wiederum der Polizei, ein zu privaten Zwecken aufgenommenes Video als Beweismaterial in einem Strafprozess zu verwenden, in dem einige der Männer aufgrund von einvernehmlich vorgenommenen sexuellen Handlungen der Körperverletzung für schuldig befunden wurden (vgl. dazu aus lesbischer Perspektive Beresford 2016).…”
Section: öFfentlichesunclassified
“…Das erlaubte es wiederum der Polizei, ein zu privaten Zwecken aufgenommenes Video als Beweismaterial in einem Strafprozess zu verwenden, in dem einige der Männer aufgrund von einvernehmlich vorgenommenen sexuellen Handlungen der Körperverletzung für schuldig befunden wurden (vgl. dazu aus lesbischer Perspektive Beresford 2016).…”
Section: öFfentlichesunclassified
“…All participants had given their consent to take part in the BDSM activity, however, despite no crime having been reported and a lack of victims coming forward, the men were charged with a variety of crimes including actual bodily harm and unlawful wounding. The judgement at trial concluded that it was not possible for an individual to give consent to sadomasochistic harm and therefore set the legal precedent of criminalising particular consensual acts, even in the absence of a victim complaint (Beresford, 2016). Although this is an older example the current law in the UK, and therefore current legal precedents relating to consent to harm, are based on this case and therefore determines that the criminal justice system is able to investigate sexual activities that are consensual and can also investigate even in the absence of a complainant (Cowan, 2011).…”
Section: Bdsm As a Stigmatised Identitymentioning
confidence: 99%